Chaos and Chaos; Complexity and Hierarchy. (26th June 2014) - Cottam, Ron; Ranson, Willy; Vounckx, Roger
Abstract : We address the characteristic complexity of large multi‐scale systems. Starting from the concept of perceptual scale, we present an ecosystemic model‐hierarchy description, which we believe is more applicable to nature than conventional hierarchical representations. Such a hierarchy, or holarchy, may be ontological or epistemological, but either case presents a layered structure alternating between local scales and locally‐scaled ecosystems that are characterized by scale‐dependent chaotic properties. Unification of a hierarchical system implies the generation of a scale‐independent property referred to as hyperscale, within which access to the different partially‐isolated system scales is transparent. We propose that this framework can be used to characterize all Natural entities, from inorganic and organic to human organizations. We conclude with an examination of processes of emergence and its counterpart demergence. Copyright © 2014 John Wiley & Sons, Ltd.